The macroeconomic effects of portfolio equity inflows - Nicholas Sander (Bank of Canada, 2023)
I provide evidence that portfolio equity inflows can have expansionary effects on GDP and inflation if not offset by monetary policy. I use a shift-share instrument to estimate equity inflows based on plausibly exogenous timing of inflows into mutual funds with heterogeneous country portfolios. For countries with fixed exchange rates, GDP rises for at least two years following an exogenous inflow with a peak effect of 0.8 percent after 18 months. This is driven by rises in investment and exports, where the latter response is inconsistent with standard expenditure switching channel mechanisms. Non-fixing countries maintain GDP roughly at the same pre-shock levels but achieve this with higher interest rates.
Keywords: E32; F32; F44; 330; International financial markets; International topics; Monetary policy; Business fluctuations and cycles